EHL-İ BEYT SEVGİSİ Nedir? Nasıl Olmalıdır? - M. Bahaüddin Varol (İstem, 2003)
Ahl al-Bayt that means people of the house of the Prophet Muhammad, has an important position in the Islamic History. The political and religious incidents which emerged after the death of the Prophet Muhammad, pushed it foreground. Hence, the Ahl al-Bayt and the affection of Ahl al-Bayt have been exploited. In order to refrain from exploiting and confusion the terms should be understood and explained properly. This study explores what and how the affection of Ahl al-Bayt is from Quran and Sunnah point of view. That is the true interpretation of ayats and hadiths and elimination of correct and sound knowledge from false one, not only indicate what the affection of Ahl al-Bayt is but also prevent from it any kind of exploitation